Interpellation - Answer - Critique? Perspectives of the Humanities and Social Sciences on Techniques of Subjectivation (KULT_online, 2014)
In this volume, subjectivation is conceptualized as a process of self-constitution and self-formation within the interplay of the self and the other. Examining these processes with regard to the techniques that contribute to their genesis shall provide a concrete starting point for empirical studies. Thus, the volume promises to give answers to those questions inevitably appearing when dealing with theories of subjectivation.